2020
DOI: 10.1177/0145561320931304
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Displaced Dental Implants in the Maxillary Sinus Using Endoscopic Approaches

Abstract: With the broad indications for dental implantation, complications rates have increased. Dental implant displacement into the maxillary sinus, although rare, can occur during the restoration of maxillary posterior teeth. We performed a 6-year retrospective review and found 3 cases with displaced implants in the maxillary sinus. Detailed information, including surgical indications and dental implant removal methods, is provided. Dental implants can be dislocated to the maxillary sinus perioperatively or postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Regarding the retrieval technique of DDIs, Chang et al (2020) [25] reported four surgical removal techniques. According to our study, IS was used in 61.2% patients in the EP, whereas ES was used in 82.5% patients in the LP, with the differences being statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the retrieval technique of DDIs, Chang et al (2020) [25] reported four surgical removal techniques. According to our study, IS was used in 61.2% patients in the EP, whereas ES was used in 82.5% patients in the LP, with the differences being statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the incidence of postoperative facial numbness was lower than that with the Caldwell-Luc technique. Otorhinolaryngologists use the fenestrated approach in the MS or modified transnasal ES by creating a small hole in the inferior nasal meatus [25,60]. Oral and maxillofacial surgeons and otorhinolaryngologists should select safe and minimally invasive surgical procedures for the retrieval of DDIs [7,10,43,44,49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of accidents that involve the MS are the oroantral communication (Polat et al, 2007) and the displacement of foreign bodies into the sinus (Toledano-Serrabona et al, 2021). In these cases, nose bleeding and sinusitis may emerge as complications (Chang et al, 2020). Large (high-volume) MS with thin walls are more prone to wall fracture and oroantral communication (Polat et al, 2007).…”
Section: Discussionmentioning
confidence: 99%